Telemedicine in rheumatology: a mixed methods study exploring acceptability, preferences and experiences among patients and clinicians. (2nd November 2021) - Sloan, Melanie; Lever, Elliott; Harwood, Rupert; Gordon, Caroline; Wincup, Chris; Blane, Moira; Brimicombe, James; Lanyon, Peter; Howard, Paul; Sutton, Stephen; D'Cruz, David; Naughton, Felix
Abstract: Objectives: The Covid-19 pandemic necessitated a rapid global transition towards telemedicine; yet much remains unknown about telemedicine's acceptability and safety in rheumatology. To help address this gap and inform practice, this study investigated rheumatology patient and clinician experiences and views of telemedicine. Methods: Sequential mixed methodology combined analysis of surveys and in-depth interviews. Between and within-group differences in views of telemedicine were examined for patients and clinicians using t-tests. Results: Surveys (patients n  = 1340, clinicians n  = 111) and interviews (patients n  = 31, clinicians n  = 29) were completed between April 2021 and July 2021. The majority of patients were from the UK (96%) and had inflammatory arthritis (32%) or lupus (32%). Patients and clinicians rated telemedicine as worse than face-to-face consultations in almost all categories, although >60% found it more convenient. Building trusting medical relationships and assessment accuracy were great concerns (93% of clinicians and 86% of patients rated telemedicine as worse than face-to-face for assessment accuracy). Telemedicine was perceived to have increased misdiagnoses, inequalities and barriers to accessing care. Participants reported highly disparate telemedicine delivery and responsiveness from primary and secondary care. Although rheumatology clinicians highlighted the importance of a quick response to flaring patients, only 55% of patients were confident that their rheumatology department would respond within 48 hours. Conclusion: Findings indicate a preference for face-to-face consultations. Some negative experiences may be due to the pandemic rather than telemedicine specifically, although the risk of greater diagnostic inaccuracies using telemedicine is unlikely to be fully resolved. Training, choice, careful patient selection, and further consultation with clinicians and patients is required to increase telemedicine's acceptability and safety. Trial registration: This telemedicine study is part of a pre-registered longitudinal multi-stage trial, the LISTEN study (ISRCTN-14966097), with later Covid-related additions registered in March 2021, including a pre-registered statistical analysis plan.